The Use of Speech Acts Among Front Office Students in Learning EFL at SMK Negeri 2 Singaraja - Putu Wahyu Sudewi (Journal on Education, 2019)
Abstract This research was intended to analyze: a) the locutionary act used among prospective front officer students to express front officer tasks in terms of speech acts category, b) the speech styles used among prospective front officer students to express front officer tasks in terms of politeness and impoliteness. c) the errors committed in their speech acts in terms of grammar, diction, and appropriateness. The subjects of the study were the front office students of grade twelve at SMK Negeri 2 Singaraja. It was designed as a descriptive qualitative research and employed data elicitation, recording, data transcription and coding as methods of data collection. The data analysis was affiliated with Bach and Harnish’s (1979) speech acts theory, Geoffrey Leech’s (1983) politeness principle theory and was done following Miles and Huberman’s (1994) interactive model of data analysis. This study found that the highest frequency of speech acts produced by prospective front officer students was directives (67.8%) and then followed by acknowledgments (14.9%), constatives (14.4%) and the lowest frequency was commissives (2.9%). Keywords: speech acts, prospective front officer students, learning EFL, Abstrak Penelitian ini bertujuan untuk menganalisis: a) tindakan locutionary yang digunakan diantara siswa calon petugas front office untuk mengungkapkan tugas mereka dalam kategori tindak tutur, b) gaya bicara yang digunakan diantara siswa calon petugas front office untuk mengungkapkan tugas mereka dalam istilah sopan dan tidak sopan. c) errors yang dilakukan dalam tindak tutur mereka dalam hal tata bahasa, diksi, dan ketepatan. Subyek penelitian ini adalah siswa akomodasi perhotelan kelas dua belas di SMK Negeri 2 Singaraja. Penelitian ini dirancang sebagai penelitian deskriptif kualitatif dan memakai data elicitation, perekaman, transkripsi data dan coding sebagai metode pengumpulan data. Analisis data dihubungkan dengan Bach dan Harnish (1979) teori tindak tutur, Geoffrey Leech (1983) teori prinsip prinsip kesopanan dan mengikuti Miles and Huberman (1994) model interaktif dari analisis data. Hasil penelitian menunjukan bahwa frekuensi tertinggi dari tindak tutur yang dihasilkan oleh siswa calon petugas front office adalah directives (67,8%) dan diikuti oleh acknowledgments (14,9%), constatives (14,4%) dan frekuensi terendah commissives (2,9%). Kata kunci: tindak tutur, siswa calon petugas kantor depan, belajar EFL,